A FREEWARE PACKAGE FOR THE ANALYSIS AND INTERPRETATION OF COMMON-OFFSET GROUND PROBING RADAR DATA, BASED ON GENERAL PURPOSE COMPUTING ENGINES - Tzanis, A.; Kafetsis, G. (Bulletin of the Geological Society of Greece, 2004)
The Ground Probing Radar (GPR) has become an invaluable means of exploring shallow structures for geoscientific, engineering environmental and archaeological work. At the same time, GPR analysis software is mostly proprietary and expensive. The academic freeware community has been slow to react the limited free software is usually highly focused and generally unorganized. Herein we report the beginning of an attempt to remedy this situation with a cross-platform freeware analysis and interpretation package, which can also be expandable and customizable to the requirements of a particular user with relatively little programming effort. Almost ideal platforms for the development of such a kind of software are general purpose computing engines, such as MATLAB ™ and/or OCTAVE. These provide two very similar, cross-platform and complete environments for the development of advanced analysis software. We have designed a two-layered software system. The Bottom Layer comprises a set of self-contained and self-documented functions to handle, visualize, process and interpret GPR data and is expandable with addition of a user's own functions. The Top Layer organizes these functions, automating data management and streamlining the flow of work by means of a GU Interface. At the present stage of development, this GPR analysis offers a decent and in many respects advanced means of treating and interpreting common-offset data; future releases may even become competitive, if maintained and developed by collective effort along the spirit of the GNU project.